Utilization of polar metabolite profiling in the comparison of juvenile wood and compression wood in loblolly pine (Pinus taeda) - Yeh, T.F; Morris, C.R; Goldfarb, B; Chang, H.M; Kadla, J.F (Tree physiology, 2006)
Juvenile wood (JW) of conifers is often associated with compression wood (CW), with which it is sometimes believed to be identical. To determine whether JW and CW can be distinguished metabolically, we compared gas chromatographic profiles of 25 polar metabolites from rooted cuttings of a single loblolly pine (Pinus taeda L.) clone raised in controlled environment chambers and subject to three treatments: (1) grown erect with minimal wind sway (control); (2) swayed by wind from oscillating fans; and (3) with 30-cm growth increments successively bent at an angle of 45° to the vertical. Profiles were compared by principal component analysis. Substantial increases in abundances of coniferin and p-glucocoumaryl alcohol separated immature JW-forming xylem tissues of the control trees from the CW-forming xylem of the bent and swayed trees.